Naprężenia Dynamiczne w Nieskończenie Długim Walcu, Wywołane Działaniem Zmiennej Temperatury - Woelke, S. (Engineering Transactions, 1967)
The problem under consideration is the dynamic problem of thermal stresses in an infinite cylinder the surface of which is heated at a periodically varying temperature. In addition to the solution for any frequency of the temperature variation, the problem of resonance is solved for a temperature varying at a resonance frequency. A few resonance frequencies are determined. As a result on the analysis it is found that the resonance frequencies of the temperature lie outside the frequency range that can be expected in engineering problems.